Milking management clinics - Dunham, James R.; Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
Thirty Milking Management Clinics have been conducted at various on-farm locations. The clinics have demonstrated that good milking techniques can result in an additional 1891 lb milk yield/cow in a 10-mo lactation and an increased milk flow rate of 0.9 lb/min. Additional demonstrations include: I) teat dipping techniques, 2) proper sanitation programs, 3) antibiotic sensitivity culturing, 4) residue avoidance programs, 5) dry cow treatment techniques, and 6) milking equipment evaluation.
Keywords: Dairy; Milking management; Milk secretion; Milk let-down